1989
DOI: 10.1557/proc-176-577
|View full text |Cite
|
Sign up to set email alerts
|

The Solubility and Sorption of Uranium (VI) in a Cementitious Repository

Abstract: The solubility behaviour of uranium(VI) has been studied in a number of waters representative of the pore waters to be expected in candidate repository backfill concretes and also in solutions of calcium and sodium hydroxides. The sorption of uranium has been studied on one of these candidates, a Portland cement with a slag filler. The same cement has been hydrothermally treated to simulate the temperature conditions in the repository and the product used for comparative studies.The paper describes the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…Some experiments were made using subsequent filtration (0.22 µm Millipore  ). The short shaking time (3 days) is compatible with the observation of Brownsword et al [7] who showed through a kinetic study (1, 20 and 33 days) that the measured solubilities did not change significantly with time.…”
Section: Solubility Of U(vi) In Cement and C-s-h Solutions And Sorptisupporting
confidence: 90%
See 1 more Smart Citation
“…Some experiments were made using subsequent filtration (0.22 µm Millipore  ). The short shaking time (3 days) is compatible with the observation of Brownsword et al [7] who showed through a kinetic study (1, 20 and 33 days) that the measured solubilities did not change significantly with time.…”
Section: Solubility Of U(vi) In Cement and C-s-h Solutions And Sorptisupporting
confidence: 90%
“…U(VI) sorption after 14 days, and desorption after 6 days, in suspensions containing CEM I and CEM V degraded cement pastes and C-S-H phases. Literature data are: a -Aged Concrete [10]; b -Fresh concrete: OPC, BFS, fly ash ... [10]; c -Different types of cement: pure or blend of OPC/BFS/PFA [7]; d -Hydrothermaly degraded cements [7]; e -Different types of concrete: OPC/lime/limestone aggregates [12]. dation state of the cement.…”
Section: Evolution Of R D With Cement Degradationmentioning
confidence: 99%
“…The uranium dataset is largely based on that proposed by Lemire [13] except for the uranium(VI) hydrolysis dataset, which has been edited to remove the anionic U0 2 (0H)4~ and (U0 2 ) 3 (0H)7 species. There is some experimental support in the literature for the existence of these species, however recent uranium(VI) solubility studies at Harwell [14] suggest they are formed to a lesser extent than predicted by the Lemire data. The data from reference [14] were used to refine the constant proposed by Lemire for the formation of the U0 2 (OH) 2 species:…”
Section: (B) Thermodynamic Databasementioning
confidence: 93%
“…Pointeau et al [17] report sorption distribution ratios (R d values) ranging between 3 Â 10 4 L kg À1 and 1.5 Â 10 5 L kg À1 . In contrast, several studies on the immobilization of uranium by hardened cement paste (HCP) at ambient temperature [17][18][19][20][21][22][23] and at elevated temperature [24] have been undertaken. Sorption was reported to be strong with R d values typically varying between 10 4 L kg À1 and 10 5 L kg À1 .…”
Section: Introductionmentioning
confidence: 99%